ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN PADA TOKO ONLINE KNITTING WAREHOUSE - Widowati, Retno; Safira, Syahra (Universitas YPPI Rembang, 2023)
This research was conducted to find out the marketing strategy for the Knitting Warehouse online shop. The purpose of this research is to find out marketing strategy analysis, find out obstacles and solutions in solving problems. Data collection is through observation, namely directly observing the object being studied. There are many obstacles that occur and emerge, namely competing products, websites that often have problems, building a good image for customers and increasingly diverse promotions. The solution to increase sales volume is still less effective, however, by analyzing an effective marketing strategy, it can be done using an analysis using the marketing mix (Marketing Mix)7p. Through marketing strategy analysis, the Knitting Warehouse online store can evaluate the effectiveness of the sales strategies that have been implemented and identify potential improvements or changes that are needed.Key Word: marketing mix, sales volume